THE MARGINALIZATION OF WOMEN AND CHILDREN IN EAST KALIMANTAN COAL MINING INDUSTRY - Anak Agung Sagung Dyah A.N.A.; Elisabeth Dewi (Universitas Jenderal Ahmad Yani, 2019)
This paper aimed to describe women and children marginalization in coal mining companies in East Kalimantan. Coal mining activities which is expected to support the national income of Indonesia, in fact, don’t give benefits to all parties, especially women and children. Local communities around the mining area are only obtained the environmental damage caused by the mining companies (in this case the mine excavation holes). This paper is expected to contribute in describing the impact of privatization by the government through ecofeminism lens.